Negócios de impacto socioambiental e mídias digitais: os efeitos da comunicação na base da pirâmide - Lana, Cibele Piazzarolo (2024)
Increasingly, albeit at different levels of maturity, the private sector has been aligning its strategies with the Sustainable Development Goals (SDGs). In this context, we find Socioenvironmental Impact Businesses (SIBs), which embrace the SDGs and their respective socioenvironmental challenges and goals as the core business of their enterprises. However, reports from Pipe.Lab, a leading research and applied knowledge source on the socioenvironmental impact market in Brazil, indicate that these organizations face challenges in marketing communication, predominantly directed at the bottom of the pyramid target audience (in situations of socioeconomic vulnerability), either directly or indirectly. Therefore, this study aims to understand how this consumer base at the bottom of the pyramid decodes social transformation through marketing communication via the social media of Socioenvironmental Impact Businesses (SIBs). Using Transformative Consumer Research (TCR), an approach that sees marketing as a promoter of well-being and quality of life, semi-structured interviews were conducted with 14 low-income consumers from two SIBs. Content analysis suggests that marketing communication does not fully align with the social transformation proposed by the companies, creating a division of feelings between what the company is and what it communicates through its digital channels. Furthermore, the results reveal audience preferences in terms of language, imagery, and message formats. This research aims to contribute to the evolution of the topic in academia and produce a technical product in the form of a manual, enabling marketing managers in SIBs to address their marketing communication challenges with the bottom-of-the-pyramid audience more effectively.